Quantitative and Qualitative Analysis of Plumbagin in the Leaf and Root of Plumbago europaea Growing Naturally in Kurdistan by HPLC - Hazhar M. Muhammad; Kawkab Y. Saour; Alaadin M. Naqishbandi (College of Pharmacy University of Baghdad, 2017)
Plumbago (Plumbaginaceae) is a genus of 10-20 species of flowering plants used in traditional Indian medicine, native to warm temperature to tropical regions of the world. The roots of Plumbago europaea, the Iraqi species of Plumbago, have been used for the treatment of cancer, rheumatoid arthritis, and dysmenorrhea. The main active constituents from dried powdered leaves and roots of Plumbago europaea were extracted by Soxhlet apparatus using ethyl acetate, the main active constituent was characterized by spectroscopic analysis (IR, 1H NMR, and 13C NMR)   as plumbagin. Quantitative and qualitative study of plumbagin in the roots and leaves extracts was carried out by HPLC technique  using analytical column (Eurospher 100, C18, 5 Âµm, 250 x 4.6 mm)  with 10% solvent (B) isocratic elution of methanol (solvent A) and water (solvent B) at flow rate 0.75 ml/min and detection wave length of 270 nm. The percentage of plumbagin in the root and leaf extracts was recorded to be (1.9 %) and (1.5 %) respectively. Keywords: Plumbago europaea, plumbagin, HPLC